Formulation and In-Vitro Evaluation of Fexofenadine HCl Nano Lipid Based Formulation - B, Fathima; S, Chukka (Journal of Neonatal Surgery, 2025)
Introduction: Nanostructured lipid carriers (NLC’s) are second-generation lipid nanoparticles that are used as alternative colloidal drug carriers. Fexofenadine HCl, is a long-acting antihistamine that is used to treat annual hay fever, angioedema and chronic autoimmune hives. Methods: Fexofenadine NLC was prepared using the ultra-sonication method followed by hot homogenization. Total six formulations were developed. All the formulations were evaluated for particle size analysis, encapsulation efficiency and drug release studies. The physical stability was conducted on optimized formulation for 3 months. Results: The particle size of all the formulations was found in the range of 124± 0.12 to 231.4± 0.12 nm. The PDI was ranged between 0.204 ±0.002 to 0.273± 0.001. The zeta potential values for all the NLC formulations were found to be within the range of -22.21± 2.23 to -28.17± 1.31. Based on the physicochemical properties, F6 formulation was selected as the optimized formulation. Conclusion: Fexofenadine NLC was developed using ultrasonication method and hot homogenization. The optimized formulation (F6) showed highest encapsulation efficiency, drug release and was stable for 3 months.